A Novel Unilateral Bi/Multi‐Portal Endoscopic Transforaminal Interbody Fusion Utilizing Uniaxial Spinal Endoscope Instead of Arthroscope: Technical Note and Preliminary Clinical Results - Liyu Yang; Long Zhou; Min Qiu; Feng Liang; Liqing Yang; Qin Fu; Gen Ba (Orthopaedic Surgery)
ABSTRACT Background Currently, traditional UBE surgery, which is based on arthroscope, has been increasingly employed for complex lumbar degenerative diseases. However, this approach is associated with complications such as intraoperative dural sac tears, nerve root injuries, and postoperative epidural hematomas. In response to these challenges, we propose a novel technique utilizing uniaxial spinal endoscope to replace arthroscope—Unilateral Bi/Multi‐Portal Endoscopy (UME). This new method has successfully treated complex lumbar disc herniation and spinal stenosis, resulting in improved postoperative outcomes and a reduction in complications. Based on the previous findings, we utilized uniaxial spinal endoscopy as the primary operating method, with the assistance of multi‐portal endoscopic techniques (UME‐TLIF), to perform transforaminal lumbar interbody fusion. The feasibility and preliminary clinical results have been presented in this paper. Methods A total of 18 patients (8 men and 10 women, aged 52.6 ± 15.29 years) diagnosed with lumbar degenerative diseases, such as giant lumbar disc herniation, severe lumbar spinal stenosis, or lumbar spondylolisthesis, were included in this study from January 2022 to March 2023. Various parameters including operation time, ambulatory time, intraoperative fluoroscopy times, hospitalization days, and complications were recorded during the perioperative period. Clinically relevant symptoms were evaluated and documented 1, 3, 6, and 12 months postoperatively. Visual analogue scale (VAS) scores for lower back pain and leg pain, as well as the Oswestry disability index (ODI), were measured. The extent of lumbar interbody fusion was assessed using lumbar X‐ray and CT scans at the 12‐months follow‐up. MRI was performed to assess the degree of nerve decompression in patients at the same time points. The paired t‐test or Wilcoxon signed‐rank test were used as statistical methods. Results The single‐segment UME‐TLIF procedure had an average operation time of 211 ± 53.3 min, and the average number of X‐rays taken during the operation was 11.78 ± 5.32. Patients were able to walk and perform functional exercises approximately 35.11 ± 8.41 h post‐surgery, and the average duration of hospital stay was 8.5 ± 2.27 days. The VAS and ODI values at each time point post‐surgery were significantly lower than the respective pre‐surgery values (p < 0.05). Two patients developed postoperative sensory disturbances which significantly improved with conservative treatment. Furthermore, a follow‐up CT scan conducted 12 months post‐surgery showed 100% fusion rate of the surgical segments in all patients. Conclusion UME‐TLIF is an endoscopy‐assisted fusion procedure that minimizes muscle damage in patients and allows early rehabilitation. This technique broadens the surgical applications of uniaxial spinal endoscope as a surgical tool, particularly benefitingpatients diagnosed with severe lumbar disc herniation and lumbar instability.